2022
DOI: 10.1002/adfm.202204354
|View full text |Cite
|
Sign up to set email alerts
|

Li‐Rich Mn–Mg Layered Oxide as a Novel Ni‐/Co‐Free Cathode

Abstract: Although Li2MnO3 exhibits high capacity via anionic oxygen redox, it suffers from rapid capacity decay owing to structural disordering accompanying irreversible Mn migration and O2 release. To promote the reversibility of the anionic redox reaction, Li1.8Mg0.3Mn0.9O3 as a novel cathode material, prepared by partially substituting Li+ and Mn4+ of Li2MnO3 with the redox‐inactive Mg2+ as a structural stabilizer is proposed. Li1.8Mg0.3Mn0.9O3 delivers a high specific capacity and energy density of ≈310 mAh g−1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…101,102 Recent reports on LRLOs sometimes applied different ratios between active materials and conductive carbon (2.5-20%), and thus increased the difficulty in making a reasonable comparison of battery performance, especially the rate capability. 54,[103][104][105] As the most commonly applied ratio, 8 : 1 : 1 of the active material, conductive carbon, and binder should be considered as a standard in LRLO research works to avoid unnecessary performance variations.…”
Section: Active Materials Loading and Coatingmentioning
confidence: 99%
“…101,102 Recent reports on LRLOs sometimes applied different ratios between active materials and conductive carbon (2.5-20%), and thus increased the difficulty in making a reasonable comparison of battery performance, especially the rate capability. 54,[103][104][105] As the most commonly applied ratio, 8 : 1 : 1 of the active material, conductive carbon, and binder should be considered as a standard in LRLO research works to avoid unnecessary performance variations.…”
Section: Active Materials Loading and Coatingmentioning
confidence: 99%
“…On the one hand, the number of 4h sites in the supercell is twice that of 2c sites, and hence the concentration of Mg in the 4h sites would be higher than that in the 2c sites. On the other hand, Lee et al 32 observed an increase in the intensity ratio of the (001) to (131) peaks in the XRD pattern of Mg-doped Li 2 MnO 3 and noted that with increasing Mg 2+ substitution, there was an increased difference value between the Li layer and the Li/Mn mixed layer, indicating that Mg 2+ tends to occupy the Li/Mn mixed layer sites.…”
Section: Introductionmentioning
confidence: 99%
“…31 To elucidate the impact of doping on the electrochemical properties of Li 2 MnO 3 , first-principles calculations have also been conducted. 21,22,[32][33][34][35][36] As for Mg doping, few investigations have been reported in the literature. In 2015, the influence of 10 cationic dopants (Mg, Ti, V, Nb, Fe, Ru, Co, Ni, Cu, and Al) at the Mn site on the phase stability, redox potential, ionic conductivity and electronic conductivity of Li 2 MnO 3 was investigated using density functional theory calculations.…”
Section: Introductionmentioning
confidence: 99%
“…资源丰富、环境友好, 是钴的潜在替代品. 铁取代 的富锂材料表现出更少的电压衰减, 但仍受制于严 重的过渡金属溶解, 循环过程中连续的不可逆容量 衰减和电压衰退, 不可逆的氧释放和较差的Li + 扩 散动力学仍有待解决 [13,[15][16][17] . 通过晶格掺杂, 表面 涂层和电解质设计等有效策略有望克服上述问题, 而掺杂因简单有效应用最为广泛, 例如, 在材料中 掺杂Mg 2+ , Al 3+ , Zr 4+ 和Ti 4+ 增大了Ni 2+ 离子从过 渡金属(TM)位点向锂离子位点迁移的热力学势 垒, 降低了阳离子无序的程度 [18][19][20][21] .…”
unclassified